The heating load determination of low energy buildings in northern climate - Venckus, Nerijus; Bliūdžius, Raimondas; Poderytė, Jurga; Burlingis, Arūnas (Journal of Civil Engineering and Management, 2012)
Low energy buildings require an efficient thermal insulation of the envelopes ensuring minor heat losses; such buildings must be tight in order to avoid heat losses due to over-infiltration. Installation of a heating recovery system compensates for some heat used for heating the ventilation air. The design solution of transparent envelopes of low energy buildings determines significant solar heat gains that compensate for a part of heat losses through the envelopes and ventilation systems. Taking into account these properties of low energy buildings, the modeling of indoor temperatures of such building was carried out at varying outdoor temperatures and power of the heating system. On the grounds of the obtained results, it was determined that a lower heat source power than the one determined according to the outdoor temperature of the coldest five-day period can be used to meet the indoor microclimate requirements in a low energy building. In this way, the expenses of heating system installation are reduced and the operational efficiency of the heat source is increased.